The desert green algae Chlorella ohadii thrives at excessively high light intensities by exceptionally enhancing the mechanisms that protect photosynthesis from photoinhibition. (28th April 2021) - Levin, Guy; Kulikovsky, Sharon; Liveanu, Varda; Eichenbaum, Benjamin; Meir, Ayala; Isaacson, Tal; Tadmor, Yaakov; Adir, Noam; Schuster, Gadi
SUMMARY: Although light is the driving force of photosynthesis, excessive light can be harmful. One of the main processes that limits photosynthesis is photoinhibition, the process of light‐induced photodamage. When the absorbed light exceeds the amount that is dissipated by photosynthetic electron flow and other processes, damaging radicals are formed that mostly inactivate photosystem II (PSII). Damaged PSII must be replaced by a newly repaired complex in order to preserve full photosynthetic activity. Chlorella ohadii is a green microalga, isolated from biological desert soil crusts, that thrives under extreme high light and is highly resistant to photoinhibition. Therefore, C. ohadii is an ideal model for studying the molecular mechanisms underlying protection against photoinhibition. Comparison of the thylakoids of C. ohadii cells that were grown under low light versus extreme high light intensities found that the alga employs all three known photoinhibition protection mechanisms: (i) massive reduction of the PSII antenna size; (ii) accumulation of protective carotenoids; and (iii) very rapid repair of photodamaged reaction center proteins. This work elucidated the molecular mechanisms of photoinhibition resistance in one of the most light‐tolerant photosynthetic organisms, and shows how photoinhibition protection mechanisms evolved to marginal conditions, enabling photosynthesis‐dependent life in severe habitats. Significance Statement: Analysis of the photosynthetic properties of a desert algae that thrive at extreme high light intensities revealed protection from photoinhibition driven by the remarkable enhancement of three protection mechanisms.